TIROS-N/NOAA エイセイ ノ TOVS ニ ヨル ナンキョク タイキ ノ オゾン ゼンリョウ ノ ドウシュツ - 山内, 恭; ヤマノウチ, タカシ; 岩品, 伊佐雄; イワシナ, イサオ; 瀬尾, 洋一; セオ, ヨウイチ; Yamanouchi, Takashi; Iwashina, Isao; Seo, Yoichi (1984)
P(論文) 南極昭和基地で受信されたTIROS-N/NOAA系気象衛星のTOVSデータから, 回帰法によって, オゾン全量の導出を試みた。HIRS/2の中で, オゾン9.6μm帯にあるチャンネル9のほか, チャンネル1,2,3と8を使った。回帰係数は, 昭和基地のドブソン観測値を使って定めた。1981年2月から1982年1月にかけて, NOAA-6,-7の約50軌道のデータを解析した。こうして求めたオゾン量は, 昭和基地ではドブソン値との平均2乗誤差が3-13DU ((10)^<-3>・atm・cm)であった。オゾン全量の水平分布も求め, 南極点においても, 衛星による値と地上でのドブソンによる値とがよい一致を示した。 A simple regression method is applied to derive the total ozone amount from the TOVS data of TIROS-N/NOAA meteorological satellites received at Syowa Station, Antarctica. Besides channel 9 located in the ozone 9.6μm band, channels 1,2,3 and 8 of HIRS/2 are used. Regression coefficients are determined against Dobson measurements at Syowa Station. Data from 50 orbits of NOAA-6 and -7 are analyzed for 1981-1982. RMS errors of retrieved ozone amounts are 3 to 13 DU ((10)^<-3>・atm・cm) at Syowa Station. Horizontal distributions of the total ozone amount are also given and fairly good agreements are seen at the South Pole between the ozone amounts derived from satellites and ground Dobson measurements. departmental bulletin paper